Establishing a New International Standard for Natural Dyed Textile Goods [Natural Organic Dye Standard (NODS)] - Recep Karadag (Journal of Natural Fibers, 2023)
Environmental awareness has become more important among individuals and societies in recent years. The increasing awareness and sensitivity to the environment have made the reintroduction of natural dyes in the textile industries even more important. To date, natural dyes have been employed in the textile industries for years, and their use is now increasing rapidly. However, there is no standard or no criteria for textiles colored with natural dyes despite the fact that individual and institutional customers, textile brands, and other bodies have been advocating for such as standards. For this reason, NODS (Natural Organic Dye Standard) is required like GOTS (Global Organic Textile Standard), OECO-TEX (International Association for Research and Testing in the Field of Textile and Leather Ecology), and other certificates. The NODS includes a list of natural dye resources (dye plants, dye insects, dye mollusks, dye lichens, and dye fungi), natural coloring compounds, mordant materials, auxiliary substances, and index of fastness properties of dyes used in textiles, and list of prohibited, and restricted substances. The standards also specify test and analysis methods.